Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, spring 1999 - Proescholdt, Market al (1999)
An annotated list of birds sighted by Mark Proescholdt and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed/flatbed